Alterations in strength of the shoulder rotators in young elite swimmers - Gustavo Antonio Meliscki; Luciana Zaranza Monteiro; Marcos Antonio Furumoto; Guilherme Henrique Ramos Lopes; Estela Cristina Carneseca; Everaldo Encide de Vasconcelos
Abstract Introduction: Shoulder muscle strength imbalance is considered a risk factor for shoulder injuries in athletes, especially in sports involving arm movements above the head. Objective: To assess the strength of the external rotators (ER) and internal rotators (IR) of the shoulder in elite swimmers, to determine possible differences between the dominant and non-dominant limbs, and to calculate the shoulder IR/ER ratio. Methods: Fifteen athletes participated in the study from age 20 ± 2 years, mass of 76 ± 4 kg, stature of 1.83 ± 4 cm, and BMI of 22 ± 1 kg/m2. Duration of practice of 10.74 ± 4.03 years; training frequency 5.95 ± 0.22 days/week, 2.07 ± 0.41 hours/day; and weekly number of meters swum 34.905. An isometric dynamometer (Globus Ergo System®, Codognè, Italy) was used to assess ER and IR strength. Data were analyzed using descriptive statistics (mean and standard deviation), paired-sample t-test, Pearson's correlation coefficient and the Statistical Package for Social Sciences software (SPSS), version 16.0. Results: IR and ER strength was lower in the left than in the right shoulder of the swimmers (p < 0.05). Additionally, ER strength ratio was higher than IR strength ratio (p < 0.05). Conclusion: The results showed that the swimmers had an alteration of the shoulder ER/IR ratio, especially in the dominant limb.